2009
DOI: 10.1021/jp8082985
|View full text |Cite
|
Sign up to set email alerts
|

Ionization of Anthracene Followed by Fusion in the Solid Phase under Intense Nonresonant Femtosecond Laser Fields

Abstract: Fused anthracene cation and a series of anthracene−C n H m cluster-like products were observed on irradiation with nonresonant femtosecond pulses at 1.4 μm. Ionization of polycrystalline anthracene revealed strikingly different features such as the absence of multiply charged molecular ions, the appearance of H+ and C+ at low intensity without the formation of C n H m fragment ions, C n H m -attached and detached molecular ions, and multimer cation formation, compared with the gas-phase experiments. The fusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…As a result, we compare the results of studies with isolated (1.4 μm, 130 fs, 2×10 13 -2×10 14 W cm −2 ) [333] and crystalline (1.4 μm, 56 fs, 5×10 12 -2×10 13 W cm −2 ) [334] anthracene exposed to intense femtosecond laser pulses, and anthracene clusters exposed to the energetic projectiles (Xe 20+ , 360 keV) [129]. In the case of isolated anthracene, the triply charged molecular cation is formed with little fragmentation by using a femtosecond laser pulses ( Fig.…”
Section: Carbon Based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, we compare the results of studies with isolated (1.4 μm, 130 fs, 2×10 13 -2×10 14 W cm −2 ) [333] and crystalline (1.4 μm, 56 fs, 5×10 12 -2×10 13 W cm −2 ) [334] anthracene exposed to intense femtosecond laser pulses, and anthracene clusters exposed to the energetic projectiles (Xe 20+ , 360 keV) [129]. In the case of isolated anthracene, the triply charged molecular cation is formed with little fragmentation by using a femtosecond laser pulses ( Fig.…”
Section: Carbon Based Materialsmentioning
confidence: 99%
“…M + , M2 + , and M3 + denote the monomer, dimer, and trimer of molecular ions, respectively. Adapted with permission from Ref [334]…”
mentioning
confidence: 99%
“…The different PAH growth mechanisms, considered in combustion science, rely on hydrogen abstraction followed by addition of a small hydrocarbon group (acetylene, phenyl, methyl, or vinyl) . Starting from the condensed phase, oligomers of PAH molecules are formed by pyrolysis. , Growth of PAH molecules can also be induced by laser irradiation of suitable solids. , …”
mentioning
confidence: 99%
“…6,7 Growth of PAH molecules can also be induced by laser irradiation of suitable solids. 6,8 Small PAH molecules are formed in the gas phase via lowtemperature ion−molecule reactions. 9−11 Polymerization of hydrocarbons induced by electron and photon impact ionization of molecular clusters has also been demonstrated.…”
mentioning
confidence: 99%
“…Although more than several photons are required for ionization, the efficiency can be improved by using a laser with a high peak power. When the molecular ion has no absorption band in the NIR region, fragmentation can be reduced and a molecular ion can be efficiently observed. It is reported that a laser with a lower pulse energy and a shorter pulse width is preferential for observing a molecular ion and that a ring-shaped molecule is more stable against a linear molecule and is resistive against the fragmentation. ,, In addition, a linearly polarized beam has been reported to be more useful to reduce the fragmentation against the circularly polarized beam . However, many types of pesticides have complicated chemical structures, and their ionization mechanisms have not yet been studied in detail.…”
mentioning
confidence: 99%